Clostridium difficile infection in low‐ and middle‐human development index countries: a systematic review. Issue 10 (31st August 2017) - Forrester, Joseph D.; Cai, Lawrence Z.; Mbanje, Chenesa; Rinderknecht, Tanya N.; Wren, Sherry M.
Abstract: Objective: To describe the impact and epidemiology of Clostridium difficile infection (CDI) in low‐ and middle‐human development index (LMHDI) countries. Method: Prospectively registered, systematic literature review of existing literature in the PubMed, Ovid and Web of Science databases describing the epidemiology and management of C. difficile in LMHDI countries. Risk factors were compared between studies when available. Results: Of the 218 abstracts identified after applying search criteria, 25 studies were reviewed in detail. The weighted pooled infection rate among symptomatic non‐immunosuppressed inpatients was 15.8% (95% CI 12.1–19.5%) and was 10.1% (95% CI 3.0–17.2%) among symptomatic outpatients. Subgroup analysis of immunosuppressed patient populations revealed pooled infection rates similar to non‐immunosuppressed patient populations. Risk factor analysis was infrequently performed. Conclusions: While the percentages of patients with CDI in LMHDI countries among the reviewed studies are lower than expected, there remains a paucity of epidemiologic data evaluating burden of C. difficile infection in these settings.